2009
DOI: 10.1111/j.1439-0272.1991.tb02576.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological effects of the catecholestrogens on cells of the seminiferous tubules of Sprague-Dawley rats

Abstract: Estradiol-17P (E,) and rhe two catecholestrogens 2-OHE, and 4-OHE2, when daily administered at low doses of 10-40 ng/rat, were cytotoxic to the seminiferous epithelium. The structural changes seen after seven days exposure included abnormal meiotic type I1 cells with uneven chromosome distribution, the formation of binucleated and multinucleated giant cells, of which many were sloughed into the lumina of the seminiferous tubules. The effect of the 4-OHE, metabolites were always more pronounced than that of 2-O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Female rats exposed prenatally to testosterone have altered reproduction later in life and no nipple development (i.e., masculinized mammary morphology), suggesting that gestational exposure to testosterone severely inhibits the normal development of females, rendering them unable to nurse their offspring [ 10 ]. In the male rat, exposure to estradiol was reported to induce morphological lesions and spermatogenic arrest [ 11 ]. Besides, the continued and massive intake of estrone may enhance tissue deposition and lead to obesity [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Female rats exposed prenatally to testosterone have altered reproduction later in life and no nipple development (i.e., masculinized mammary morphology), suggesting that gestational exposure to testosterone severely inhibits the normal development of females, rendering them unable to nurse their offspring [ 10 ]. In the male rat, exposure to estradiol was reported to induce morphological lesions and spermatogenic arrest [ 11 ]. Besides, the continued and massive intake of estrone may enhance tissue deposition and lead to obesity [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The exact mechanisms of this duality are not understood completely, but they may depend on the expression of specific cell estrogen receptor variants (17). Alternatively, tamoxifen is converted to biologically active metabolites in the liver, after oral treatment, some of which have been reported to have greater affinity for the estrogen receptors in vitro and thus have the potential to modulate the tamoxifen-induced effects in vivo by exerting synergistic or antagonistic effects (18)(19)(20).…”
mentioning
confidence: 97%
“…For several years, the presence of regulated hormone residues in food that exceeds the maximum prescribed limits has been a concern for public health. Animal studies have reported adverse effects, such as altered reproductive development, due to prenatal sex steroid hormone exposure (Seegers, van Aswegen, Nieuwoudt, & Joubert, 1991). Additionally, hormones derived from animal products have endocrine-disrupting effects in humans (Nakajima et al, 2015); therefore, steroid hormones may have a function in multiple diseases, including cancer (Krieger, 2008;Nachman & Smith, 2015).…”
Section: Re Sults and Discussionmentioning
confidence: 99%